Compensation to clinical trial participants in India: A gap analysis - Urooj, Mohd; Husain, Gulam Mohammed; Khan, Mohammad Ahmed; Kazmi, Munawwar Husain (International Journal of Pharmaceutical Investigation)
The recent amendments notified by the Government of India, for conducting clinical trial, is greatly appreciable as promoting safety and well‑being of human subjects. These rules clearly state that medical management of injuries in clinical trials is mandatory, and clinical trial‑related injury or death needs to be compensated over and above the medical management. These rules need to be reconsidered for simplification and better understanding of issues regarding compensation. There is a need of clarity at some points which should be discussed with all stakeholders for better understanding of current regulations. In our view, attention must also be given to academic investigators, during discussion to promote availability of cost‑effective treatment in India.
Keywords: Adverse event; ethics; injury/death